INFLUENCIA DEL CULTIVO DE LUPINUS LUTEUS L. EN LA DENSIDAD DE INÓCULO DE PHYTOPHTHORA CINNAMOMI EN SUELOS DE DEHESA - SERRANO, M S; SÁNCHEZ, M E; DE VITA, P; CARBONERO, M D; TRAPERO, A; FERNÁNDEZ-REBOLLO, P (Actas de la XLVIII RC de la SEEP. Huesca La multifuncionalidad de los pastos: producción ganadera sostenible y gestión de los ecosistemas, 2009)
Phytophthora cinnamomi is a pathogen causing root rot in oak trees growing in dehesa sys- tems and also in yellow lupine, a common pasture crop in western Andalusia. In dehesas show- ing different situations in terms of tree decline and disease severity in the lupines, isolation and counting of colonies of P. cinnamomi from soil samples has shown the ability of the herbaceous crop to maintain or increase the inoculum density and thus may enhance oak infections. The obtained results discourage the cultivation of this legume in dehesas with known presence of the pathogen in the soil, whether the trees are suffering the root disease or not.
Keywords: decline; Holm oak; root rot; yellow lupine

Pathogenicity of Pythium spiculum and P-sterilum on feeder roots of Quercus rotundifolia - Jimenez, J J; Sanchez, J E; Romero, M A; Belbahri, L; TRAPERO, A; Lefort, F; SÁNCHEZ, M E (PLANT PATHOLOGY, 2008)
APS
Keywords: pathogenic; Pythium spiculum; Pythium sterilum; Quercus ilex

Pathogenicity of three Phytophthora spp. causing late seedling rot of Quercus ilex ssp. ballota - SÁNCHEZ, M E; Andicoberry, S; TRAPERO, A (Forest Pathology, 2005)
Within a research project on quality of plants for forestation of agricultural lands, we studied the aetiology of a late seedling rot affecting holm oak (Quercus ilex ssp. ballota) in two forest nurseries in southern Spain. Major disease symptoms were foliage wilting and necrosis of feeder roots. Phytophthora cinnamomi, Phytophthora cryptogea and Phytophthora drechsleri were isolated from necrotic roots of holm oaks. Selected isolates of the three Phytophthora species were pathogenic to Quercus ilex ssp. ballota and Quercus suber seedlings in artificial inoculations. Soil flooding conditions were essential for infection and root rot development. There was no host specificity among the species, the isolates of P. cinnamomi being the most virulent in all inoculated plants. In these inoculations, Q. ilex ssp. ballota plants were more susceptible than those of Q. suber. This work is the first report of P. cinnamomi, P. drechsleri and P. cryptogea affecting Q. ilex ssp. ballota in forest nurseries.
Keywords: Holm oak; Nurseries (voyant); Phytophthora spp.; root rot; Soil water content

Botryosphaeria and Related Taxa Causing Oak Canker in Southwestern Spain - SÁNCHEZ, M E; Venegas, J; Romero, M A; Phillips, A J L; TRAPERO, A (Plant Disease, 2003)
ABSTRACT Although root disease caused by Phytophthora cinnamomi is considered to be the most frequent and damaging disease associated with Quercus spp. decline in southwestern Spain, cankers commonly are observed on branches of declining Mediterranean Quercus spp. in this region. In surveys carried out in eight declining Quercus forests, strips of necrotic inner bark were common on diseased branches. Botryosphaeria stevensii, B. dothidea, and Diplodia sarmentorum consistently were isolated from these branches. Isolates of all three species caused cankers when inoculated onto excised Quercus branches. Inoculations on healthy branches in the field also induced canker development, but only B. stevensii caused lesions that girdled and killed the branches. The optimum temperature for in vitro growth of B. stevensii and B. dothidea was above 25°C, with slow growth at 35°C. In contrast, D. sarmentorum had an optimum temperature for growth of about 21°C, and did not grow at 35°C. The common occurrence and wide distribution of these pathogens, their association with cankers, and their ability to infect Quercus spp. suggest that they may contribute to the Quercus spp. decline in southwestern Spain.
doi: 10.1094/PDIS.2003.87.12.1515
Keywords: Botryosphaeria ribis; diplodia mutila; Fusicoccum aesculi; Otthia spi- raeae; Quercus ilex; Quercus suber

Bioensayo para la detección de PHYTOPHTHORA CINNAMOMI EN EL SUELO DE RODALES AFECTADOS POR LA SECA DE QUERCUS - HERMOSO, R; SÁNCHEZ, E; TRAPERO, A (III Congreso Forestal Español, 2001)
The isolation of Phytophthora spp. from soil samples is often difficult, even using indirect methods which combine baiting techniques and selective media. Apple or avocado fruits or carnation petals are some of the most common baits used for the isolation of P. cinnamomi from infested soils where Quercus ilex and Q. suber have been affected by root rot and decline. However, the use of these baits has serious limitations because of the contamination by several fungi and bacteria. The aim of this work was to improve the baiting technique for the pathosystem P. cinnamomi / Quercus spp. The effect of different factors, including several baits (leaves, fruits, cotyledons, radicles), the soil:water dilution, and the incubation time, was checked using a soil mixture artificially infested with several isolates of P. cinnamomi. The most effective baiting method included baits of eucalyptus phyllodium pieces (Eucalyptus globulus and less effective E. camaldulensis), 1:6 soil:water relation, and 4 days incubation period. The efficiency of this method has been tested for the detection of P. cinnamomi in naturally infested soil samples from fields where the root rot caused by this pathogen had been previously diagnosed
Keywords: phytophthora cinnamomi; Quercus decline; soil detection

Etiología de las podredumbres radicales de plántulas de QUERCUS SPP. Y PINUS HALEPENSIS EN VIVEROS FORESTALES DE ANDALUCÍA - Andicoberry, S; LORA, F; SÁNCHEZ, E; TRAPERO, A (III Congreso Forestal Español, 2001)
A disease surey carried out during 1998-99 showed that holm oak (Quercus ilex) and Aleppo pine (Pinus halepensis) seedlings were affected by damping-off and root rot in three forest nurseries in Andalucía, southern Spain. A similar problem was detected affecting four species of Quercus (Q. coccinea, Q. faginea, Q. ilex, and Q. suber) in a forest nursery in 2000. Three species of Phytophthora (P. cinnamomi, P. cryptogea, and P. drechsleri) were isolated from holm oak feeder roots, and P. drechsleri was isolated from feeder roots of Aleppo pine in the first survey in 1998-99. In the second survey, Cylindrocarpon didymum was isolated from the feeder roots of the four Quercus spp. essayed, and C. destructans was isolated only from Q. faginea. Pathogenicity tests were conducted using 1 year-old healthy plants of cork oak, holm oak and Aleppo pine. Isolates of the three Phytophthora species were pathogenic to the three host species, inducing root rot and plant death. Holm oak was the most susceptible host and P. cinnamomi was the most virulent species. Isolates of Cylindrocarpon were pathogenic to cork oak and holm oak causing root rot, yellowing, defoliation, and plant death.
Keywords: Cylindrocarpon; Phytophthora; Quercus coccinea; Quercus faginea; Quercus ilex; Quercus suber